PERANCANGAN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB - Sapto Widiyanto; Sinta Rukiastiandari; Rahayu Ningsih; Silvy Amelia - Universitas BSI (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2022)
Abstract - Attendance in a restaurant is very important, because with attendance control, you will be able to check the presence of every employee. This attendance has an important role when using information technology to determine the presence of every employee and manager in the restaurant. In a manual attendance system, it will cause errors in the processing of attendance data for each employee. So there is a need for new innovations in the manual attendance system to be computerized. The attendance system that is still manual is less effective because it causes time leakage and violations, and trains employees to remain disciplined. The attendance system at KFC Harapan Indah Bekasi is currently still manual, employees are present in front of you, making it less effective and efficient. Therefore, an information system design was made, starting from the creation of entity relationship diagrams and logical record structures. After designing this website application using XAMPP software, namely Adobe Dreamweaver. The method used is the Waterfall method. The results of making a website Designing attendance at KFC there are several displays and menus that can be used by employees and managers to perform attendance. By using this system, it can help make it easier for employees and managers to do absent and recap of absences.Keywords : KFC Harapan Indah Bekasi Information System, WEB Abstrak - Absensi kehadiran dalam suatu restaurant menjadi hal yang sangat penting, dikarenakan dengan adanya kontrol absensi akan bisa mengecek kehadiran setiap karyawan. Absensi ini memiliki peranan penting jika menggunakan teknologi informasi untuk mengetahui kehadiran setiap karyawan dan manager dalam restaurant. Dalam sistem absensi yang manual akan menimbulkan kesalahan dalam proses pengolahan data kehadiran setiap karyawan. Jadi perlunya ada inovasi baru dalam sistem absensi manual menjadi terkomputerisasi. Sistem absensi yang masih manual kurang efektif dikarenakan menimbulkan kebocoran waktu dan pelanggaran, serta melatih karyawan agar tetap disiplin. Sistem absensi pada KFC saat ini masih manual, karyawan menandatangani kertas kehadiran, sehingga kurang efektif dan efesien. Oleh sebab itu di buat perancangan sistem informasi, di mulai dari pembuatan entity relationship diagram dan logical record structure. Setelah itu perancangan aplikasi website ini menggunakan sofware XAMPP, Adobe Dreamweaver. Metode yang digunakan adalah metode Waterfall. Hasil pembuatan website perancangan absensi KFC terdapat beberapa tampilan dan menu yang dapat digunakan oleh karyawan dan manager untuk melakukan absensi. Dengan menggunakan sistem ini maka bisa membantu mempermudah karyawan dan manager dalam melakukan absen dan rekap absen.Kata Kunci : Sistem Informasi KFC, WEB